2016
DOI: 10.1111/sji.12448
|View full text |Cite
|
Sign up to set email alerts
|

Role of Eosinophil Granulocytes in Allergic Airway Inflammation Endotypes

Abstract: Eosinophil granulocytes are intriguing members of the innate immunity system that have been considered important defenders during parasitic diseases as well as culprits during allergy-associated inflammatory diseases. Novel studies have, however, found new homoeostasis-maintaining roles for the cell. Recent clinical trials blocking different Th2 cytokines have uncovered that asthma is heterogeneous entity and forms different characteristic endotypes. Although eosinophils are present in allergic asthma with ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 125 publications
1
30
0
Order By: Relevance
“…Although there was a limited effect of atopy on CRS overall QoL, the presence of nasal polyps provided a more appreciable effect on patient symptoms. CRSwNP has been previously associated with poorer outcomes and decreased QoL . On further analysis of the CRSwNP population, there was no significant association between atopy and QoL measures.…”
Section: Discussionmentioning
confidence: 64%
“…Although there was a limited effect of atopy on CRS overall QoL, the presence of nasal polyps provided a more appreciable effect on patient symptoms. CRSwNP has been previously associated with poorer outcomes and decreased QoL . On further analysis of the CRSwNP population, there was no significant association between atopy and QoL measures.…”
Section: Discussionmentioning
confidence: 64%
“…Some studies have reported that patients with high FeNO levels will have a good response to corticosteroids and greater improvement in FEV 1 39,40. The reason for this result may be due to the fact that the FeNO level correlated well with the eosinophils, which is a good predictor for the response to corticosteroids 41,42. Antus et al43 pointed out that the optimum cutoff point for FENO as a predictor for significant increase in FEV 1 was 26.8 ppb (sensitivity: 74% and specificity: 75%).…”
Section: Methodsmentioning
confidence: 98%
“…Concurrent basic research studies investigating eosinophil activities in the lungs of mouse models following allergen provocation are providing support for this hypothesis and have led us and others to suggest that pulmonary eosinophils directly modulate allergic immune responses (17)(18)(19)(20)(21)(22)(23) and contribute to the remodeling/repair processes linked with the resolution of inflammation (see References 24 and 25). These studies thus suggest that eosinophil activities likely contribute to allergic pulmonary inflammation at many levels beyond their proposed role as mediators of tissue damage and cell death through the release of eosinophil secondary granule proteins (26).…”
mentioning
confidence: 99%